Analisis Kawasan Andalan Di Jawa Tengah - Pujiati, Amin (Jurnal Ilmu Ekonomi ASET, 2009)
This research aims to identify a region as a key region in Central Java . Thedata was got from the Indonesian Central Bureau of Statistics in 2001 and 2005. The analysisis used klassen typology, location quotient and regional specialization. Klassen typology resultcan be concluded that the district with the growth of Gross Domestic Regional Bruto andGross Domestic Regional Bruto per capita are high than other district which have high economicposition growth. The result analysis of location quotient, the basic sector in a key region tendsto dominate by the secondary and tertiary sector. Index regional specialization result, thedistrict which included in a key region tends to be high than the undeveloped region. Indexregional specialization result inter key region tends to the diversification sector. While, betweena key region and undeveloped region tends to the specialization sector and inter undevelopedregion.Keywords : key region, klassen typology, location quotient, regional specialization.